The Literature Movement in the Character Forming of Students of Universitas Amal Ilmiah Yapis Wamena - M, Hasriani; Tabuni, Yoel (Budapest International Research and Critics University, 2022)
Literacy movement in shaping the character of Yapis Wamena Scientific Amal University students. This study aims to determine the implementation of the Literacy Movement in shaping the character of the Yapis Wamena scientific charity university students. This research was conducted at Yapis Wamena Scientific Charity University. The method used in this research is a qualitative method, the research instrument uses observation, interviews with students. Observations were made by observing the condition of the scientific charity Yapis Wamena University and all research objects at UNAIM Wamena. Techniques Data analysis is done by means of data reduction, data presentation, and drawing conclusions or verification. The results of the study concluded that the implementation of the literacy movement in shaping the character of the Yapis Wamena Scientific Amal University students was that the literacy movement had not yet been seen as only a movement, it could be seen that students were not used to reading, writing on their own accord but students doing it on demand or as students. The formation of student character has not been maximized, this can be seen from students who do not have broad insight, students consider socializing only limited to the same ethnicity, so reading and writing literacy is still lacking, but the formation of student character is formed against the background of habits carried out in the family environment and community environment.